Kebijakan Permen ESDM No. 14 Tahun 2025: Tantangan dan Rekomendasi Tatakelola Sumur Migas Tradisional di Musi Banyuasin, Sumatera Selatan: Penelitian - Firdaus Firdaus; Widya Handini (PT PUSTAKA CENDEKIA GROUP, 2026)
Minister of Energy and Mineral Resources Regulation No. 14 of 2025 concerning Cooperation in the Management of Working Areas for Increasing Oil and Gas Production provides a new legal framework for regulating and increasing production from old oil and gas wells, which have traditionally been managed by local communities. This study examines the implementation of Regulation 14/2025 in Musi Banyuasin, Muba, South Sumatra, which has more than 22,000 smallholder wells out of a total of 45,000 national wells. A descriptive qualitative method was used, using in-depth interviews with the SKK Migas Sumbagsel, PT Petro Muba, and well owners, as well as a study of regulatory documents. The results revealed four main challenges: 1) Data validation: inconsistencies in the number of old wells versus new wells drilled by local communities post-1999. 2) Capital structure: drilling costs of Rp300 million per well encourage the dominance of hidden investors behind community cooperatives/MSMEs. 3) Technical & health, safety, security & environment (HSSE): traditional production patterns still pollute the soil and do not meet KKKS standards. 4) Institutional transition: Not a single well in Muba has transitioned to a KKKS (Contract Contract) scheme as of March 2026, unlike Batanghari, Jambi, which is already operational. It is concluded that the spirit of Ministerial Regulation 14/2025 for energy self-sufficiency has not yet been realized in Muba due to gaps in data, capital, and institutional readiness. Recommendations: Factual verification based on a Geographic Information System (GIS), a computer-based information system used to process and store geographically-based data. Furthermore, a revolving financing scheme for the Muba Regional-Owned Enterprise (BUMD) Petro, phased HSSE technical assistance, and incentives for partnering KKKS.